Peri-implant changes in papillary dimensions around zirconium dioxide implants in the esthetic area - Kniha, Kristian; Schlegel, Karl Andreas; Kniha, Heinz; Hoelzle, Frank; Modabber, Ali; Kniha, Kim (Implantologie, 2018)
The study aimed to evaluate the papilla-crown proportion around zirconia implants in a 3-year follow-up study. In addition, the correlation between the gingival biotype and changes in papillary height were evaluated. This was a prospective study of 39 patients with 40 single-gap implants assessing the papilla-crown proportion after 3 months, 1 year, and 3 years. Furthermore, correlations between the peri-implant biotypes and changes in papillary heights were evaluated. The papilla-crown proportion improved from 35.5% after 3 months to 41.7% after 3 years. Significant papillary fill was observed in the interdental space between 3 months and 3 years (P < .001). The gingival biotype had a moderate correlation to papilla height alterations. A thin or thick gingival biotype presented a very weak correlation with papilla height alterations (Spearman's rho = -0.57)
EVALuna2:35696